Experience gained from the implementation of the Saudi TraumA Registry (STAR) - Jane E. FORD; Abdulrahman S. ALQAHTANI; Shatha A. A. ABUZINADA; Peter A. CAMERON; Mark C. FITZGERALD; Ahmed S. ALENIZI; Dina FARJOU (BMC, 2020)
Abstract Background Trauma registries are essential to trauma systems, to enable collection of the data needed to enhance clinical knowledge and monitor system performance. The King Saud Medical City (KSMC) in Riyadh, Kingdom of Saudi Arabia (KSA) is aiming to become a Level 1 Trauma Centre, and required a trauma registry in order to do so. Our objective was to establish the Saudi TraumA Registry (STAR) at the (KSMC) and ready it for national deployment. The challenge was that no formal trauma data collection had occurred previously and clinicians had no prior experience of trauma registries. Methods To develop the registry, a novel 12 step implementation plan was created and followed at the KSMC. Registry criteria and a Minimum Dataset were selected; training was delivered; database specifications were written; operating procedures were developed and regular reporting was initiated. Results Data collection commenced on August 1st 2017. The registry was fully operational by April 2018, eight months ahead of schedule. During the first year of data collection an average of 216 records per month were entered into the database. An inaugural report was presented at the Saudi Trauma Conference in February 2019. Conclusions The strategy deployed at the KSMC has successfully established the STAR. In the short term, process indicators will track the development of the hospital into a Level 1 Trauma Centre. In the medium to long term the STAR will be rolled out nationally to capture the impact of public health initiatives aimed at reducing injury in the KSA. The effect of the STAR will be that the country is better equipped to deliver continuous improvements in trauma systems and quality of care.